IMPLEMENTASI TEACHING FACTORY DI SMKN 2 GEDANGSARI GUNUNGKIDUL - Yunanto, Dwi (Vidya Karya, 2016)
Abstract. Evaluation of âteaching factoryâ implementation in SMKN2 Gedangsari Gunung Kidul Yogyakarta aimed to determine the implementation of âteaching factoryâ in Boutiqe Fashion skill program of SMKN 2 Gedangsari Gunung Kidul. âTeaching factoryâ method is given by the vocational school to graduated students in order to prepare them to become more independent. This research was a descriptive study using seven parameters approach based on SED-TVET instruments. The population consisted of students, productive teachers, vice principal of curriculum affairs, and principals who run schools teaching factory. The data analyzed by using percentages. The results showed that overall SMKN 2 Gedangsari havenât implemented teaching factory in productive subject with the percentation of 41.93%, teaching factory implementation management as much as 26.67%, workshop or laboratory management as much as 64%, training learning pattern as much as 42.86%, teaching factory marketing as much as 24.00%, products and services as much as 68%, human resources in the management of teaching factory as much as 48% and industrial relations as much as 20%.Â Keywords: Teaching factory, seven parameters, vocational schoolÂ Abstrak . EvaluasiÂ pelaksanaan pembelajaran teaching factoryÂ di SMKN 2 Gedangsari Gunung Kidul Yogyakarta bertujuan untuk mengetahui proses pelaksanaan teaching factory di program keahlian Tata Busana Butik di SMKN 2 Gedangsari Gunung Kidul. Pembelajaran teaching factory diberikan oleh sekolah kejuruan pada siswa yang telah lulus agar mereka siap untuk mandiri. Penelitian ini merupakan penelitianÂ deskriptifÂ dengan mengunakan pendekatan tujuh parameter yang bersumber pada instrumen SED-TVET. Populasi penelitian adalah peserta didik, guru produktif, wakil kepala sekolah bidang kurikulum dan kepala sekolah yang menjalankan teaching factory di sekolah tersebut. Data dianalisis dengan menggunakan teknik persentase. HasilÂ penelitianÂ menunjukkanÂ bahwaÂ secara keseluruhan SMKN 2 Gedangsari belum menerapkan proses pembelajaran teaching factory dalam mata pelajaran produktif, dengan persentasi sebesar 41,93%., kegiatan managemen pelaksanaanÂ teachingÂ factoryÂ sebesar 26.67%, pengelolaan bengkel atau laboratorium sebesar 64%,Â pola pembelajaran trainingÂ sebesar 42,86%, pemasaran teaching factory sebesar 24%, produk dan jasa sebesar 68%, sumber daya manusia dalam pengelolaan teaching factoryÂ sebesae 48% serta hubungan industri sebesar 20%. Kata kunci: Teaching factory, tujuh parameter, sekolah kejuruan